Knowledge intensive computer aided design (CAD) - Tomiyama, T. (Tetsuo); Mantyla, Martti; Finger, Susan (Published by Chapman & Hall on behalf of the International Federation for Information Processing (IFIP), 1996)
Knowledge-Intensive CAD clarifies and elaborates the concepts of knowledge-intensive design and CAD. In today's advanced manufacturing environment, CAD systems should not only assist designers and engineers during product design, but also in design information for use in later stages of the process such as production, distribution and operation. This book focuses on the sharing of knowledge across life-cycle stages and organizational boundaries.